2015
DOI: 10.1002/cphc.201402734
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Additives for Organic Photovoltaic Devices

Abstract: The use of additives to improve the performance of organic photovoltaic cells has been intensely researched in recent years. However, so far, no system has been reported for the classification of additives and their functions. In this report, a system for classifying additives according to the fundamental mechanism by which they influence microstructure formation for P3HT:PCBM is suggested. The major parameters used for their classification are solubility and drying kinetics. Both are discussed in detail and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 31 publications
0
47
0
Order By: Relevance
“…Our studies do not give insight into the material specification a solvent has to fulfill for an effective SVA. Previously, we have categorized additives and found that only two solvent specific parameters are essential for casting, namely the selective solubility of a solvent for one of the semiconductors and the solvent vapor pressure at the drying temperature . It seems plausible that similar material criteria are relevant for SVA, however, this needs to be carefully studied.…”
Section: Resultsmentioning
confidence: 99%
“…Our studies do not give insight into the material specification a solvent has to fulfill for an effective SVA. Previously, we have categorized additives and found that only two solvent specific parameters are essential for casting, namely the selective solubility of a solvent for one of the semiconductors and the solvent vapor pressure at the drying temperature . It seems plausible that similar material criteria are relevant for SVA, however, this needs to be carefully studied.…”
Section: Resultsmentioning
confidence: 99%
“…Machui et al expanded the criteria proposed by Lee et al into a four category classification system based on a matrix of selective solubility of the donor (or acceptor) and the evaporation kinetics due to the vapor pressure of the additive . The researchers tested the effect of potential additives from each category (as shown in Figure ) on the performance of P3HT:PC 61 BM blend films, processed with up to 30% v/v of additive in CB.…”
Section: A Brief History Of Solvent Additives In Organic Photovoltaicsmentioning
confidence: 99%
“…We will show here that this is not a good assumption. Some solutions are intrinsically unstable or can be triggered extrinsically to aggregate [30,31]. We posit that the aging of solutions can contribute to inconsistent results published in different groups [32] and even within the same group and even when the same sample preparation procedures and experimental conditions are precisely controlled.…”
Section: Introductionmentioning
confidence: 97%